A primer on the GCF Repo Service - Paul Agueci; Leyla Alkan; Adam Copeland; Isaac Davis; Antoine Martin; Kate Pingitore; Caroline Prugar; Tyisha Rivas (Federal Reserve Bank of New York, 2014)
This primer provides a detailed description of the GCF Repo ® Service, a financial service provided by the Fixed Income Clearing Corporation. The primer is composed of an introductory note and two separate papers. The first paper focuses on the clearance and settlement of GCF Repo. These financial plumbing details are especially important because the settlement of GCF Repo has been and will continue to be impacted by the current reforms to the tri-party repo settlement platform. In particular, the authors lay out the various ways that intraday credit was used pre-reform to facilitate the settlement of GCF Repo and why this use of credit is problematic. They also describe the reforms that are planned or in effect already, and consider how these reforms affect the use of intraday credit. The second paper examines how dealers use the GCF Repo Service. The authors first describe the various strategies that dealers employ when trading GCF Repo and then use empirical analysis to quantify the predominance of these str ategies. Although they focus on different aspects of the GCF Repo Service, the two papers are complementary. This is because the strategies that dealers follow in trading GCF Repos are influenced by the clearance and settlement procedures in place. Furthermore, when gauging the risks of potential changes to the clearance and settlement of GCF Repo, it is important to take into account how GCF Repos are traded. Consequently, the papers are presented jointly so as to encourage readers to become familiar with both aspects of the GCF Repo Service.
Keywords: E42; E58; G23; G28; 330; GCF Repo; tri-party repo reforms; financial intermediation